Pengaruh Inflasi, Debt To Equity Ratio (DER) dan Total Assets Turnover (TATO) Terhadap Harga Saham Pada Perusahaan Sektor Energi Yang Terdaftar DI Bursa Efek Indonesia Tahun 2019-2022 - Yuni Mahmudah; Sri Wahyuni Mega; Diana Ambarwati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to perform analysis and find put of inflation, debt-to-equity ratio and total assets turn over on stock prices. An analysis of firms in the energy sector that were registered on the Indonesia Stock Exchange in 2019-2022. The entire population in this study consists of 83 firms. The chosen sample consisted of 6 financial reports altogether, cosen from a total of 9 companies using the purposive sampling technique. Using software Eviews 9, the panel data analysis method helps with this research. Based on research findings, it can be concluded that, Debt-to-equity ratio has negative impact on stock price, however inflation and total asset turn over do not have a significant impact. According to simultaneous test or F test, the independent variable simultaneously had statistically impact on the stock price, with a Adjusted R2 of approxiamately 0.173906, or 17.39%